Phosphate-crosslinked β-cyclodextrin polymer for highly efficient removal of Pb(ii) from acidic wastewater. (1st February 2022) - Sun, Junhua; Zhao, Xiuxian; Sun, Guoxin; Zhao, Heng; Yan, Liangguo; Jiang, Xuchuan; Cui, Yu
Abstract : Novel phosphate-crosslinked β-cyclodextrin polymer was synthesized for highly efficient Pb(ii ) removal from acidic wastewater. Abstract : The efficient and green separation of heavy metal ions from acidic wastewater is a challenging industrial problem. In this work, a novel acidic adsorbent, β-cyclodextrin phosphate polymer (β-CDPP), was synthesized by one-pot method. The β-CDPP was characterized by FT-IR, SEM, EDS, and XPS. The β-CDPP can effectively remove more than 95% Pb(ii ) from acidic wastewater (pH = 3). The adsorption of Pb(ii ) reached equilibrium in 20 min, and the maximum Pb(ii ) adsorption capacity calculated by the Sips isotherm model was as high as 576.92 mg g −1 . FT-IR and XPS analysis revealed that the adsorption mechanism of Pb(ii ) depends on the chelating effect and electrostatic interaction. The adsorbent showed good reusability evidenced by eight cycles of adsorption/desorption experiments. Meanwhile, the low concentration of Na(i ), K(i ), and Ca(ii ) had little effect on the adsorption of Pb(ii ). Moreover, the adsorbent can effectively remove a variety of mixed heavy metals from acidic wastewater including Pb(ii ), Cu(ii ), Cd(ii ), Zn(ii ), Co(ii ), and Ni(ii ). The results indicate that β-CDPP is a promising candidate for the deep treatment of acidic heavy metal-contained wastewater.